2014
DOI: 10.3136/fstr.20.1033
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quality Attributes of Strawberry Purees Processed by Power Ultrasound or Thermal Treatments

Abstract: The effect of thermal and ultrasound treatments on the physicochemical properties (pH, total soluble solids, titratable acidity, electrical conductivity, viscosity and color attributes), bioactive compounds (ascorbic acid, total pheolics and total anthocyanins) and antioxidant activity of strawberry puree was investigated. No significant difference in pH, total soluble solids and titratable acidity was observed among the treated and control samples whether thermal or ultrasound treatments were used. Ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
6
22
0
Order By: Relevance
“…observed that the anthocyanin content decreased by 5% in blackberry juice treated at 20 kHz, 100% amplitude and 25 °C for 10 min. Cheng et al . also reported a decrease of about 10% in anthocyanin content in strawberry puree treated at 20 kHz, 30% power and 40 °C for 10 min.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…observed that the anthocyanin content decreased by 5% in blackberry juice treated at 20 kHz, 100% amplitude and 25 °C for 10 min. Cheng et al . also reported a decrease of about 10% in anthocyanin content in strawberry puree treated at 20 kHz, 30% power and 40 °C for 10 min.…”
Section: Resultsmentioning
confidence: 90%
“…Ultrasound is a new type of non‐thermal processing technology. According to its frequency and power, it has been divided into two ranges: low‐frequency (20–100 kHz), high‐power (10–1000 W cm −2 ) ultrasound and high‐frequency (1–10 MHz), low‐power (<1 W cm −2 ) ultrasound High‐power ultrasound (HPU) has been identified as a potential technology to meet the FDA requirement of a 5 log 10 reduction in pertinent microorganisms occurring in fruit juices Besides, ultrasound has been reported to reduce enzyme activities, ameliorate viscosity and turbidity and improve quality parameters of juice effectively Therefore this technology has been used in carrot juice tomato juice apple juice and orange juice To the best of our knowledge, only a few researchers have studied the effect of ultrasound on strawberry juice They focused on the effects of ultrasound on the anthocyanin content, color, antioxidant capacity and microorganism inactivation of strawberry juice. However, these experiments were carried out at a fixed ultrasound power with a limited treatment time gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is controversial information related to the effects of US in physicochemical parameters of fruit-based beverages. On one hand, it has been reported that pH, TA and TSS values of different fruit juices were not affected after sonication process (Tiwari et al, 2008;Cheng et al, 2014;Abid et al, 2013;Adekunte et al, 2010). However, Bermudez-Aguirre and BarbosaCánovas (2012) observed significant changes in pH and TA after US processing of whole milk and pineapple, grape, and cranberry juices.…”
Section: Physicochemical Analysismentioning
confidence: 98%
“…In this respect, ultrasound (US) technology has received special attention because it can be cheap, simple, environmental-friendly, and effective treatment in extending shelf-life of beverages, particularly when it is combined with mild heat (thermosonication) (Abdullah, 2014). Some authors have demonstrated that US processing caused minimal impact on quality parameters and great retention of health related compounds in orange, guava, and strawberry juices, purple cactus pear, and soymilk (Abdullah, 2014;Cheng et al, 2014;Fahmi et al, 2012;Sakhale et al, 2012;Ribeiro et al, 2014;Chauhan and Patil, 2013). However, information about the effects of US treatment together with the application of mild heat on physicochemical properties and health-related compounds of mango smoothies is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Non-thermal processing can reduce microbial load, and avoid at the same time undesirable changes on food nutrients [2]. Cao et al [3] found that ultrasound treatment at a frequency of 40 kHz inhibited the decay of strawberry fruit and maintained a significant higher level of vitamin C. Cheng et al [4] observed that sonicated samples showed better retention or preservation of phenolic compounds when compared to heat-treated samples. However, recent studies have manifested that some non-thermal pasteurization alternatives may lead to the loss of vitamin C, anthocyanins, lycopene, carotenoids and flavonoids under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%